Nanochemistry and Pathological Analysis Techniques: Innovative Strategies for Detecting Biological Contaminants and Infectious Diseases - Abbas, Kazem Abdel Zahra Jabr; Nawad, Roqaya Alaa Kazem; Nawad, Batoul Alaa Kazem; Mutrb, Dalya Wady Getb; Mishko, Faisal Mahlo Qolo (American Journal of Biomedicine and Pharmacy, 2025)
Nanochemistry has emerged as a highly promising and innovative method for the highly sensitive and remarkably rapid diagnosis of a wide variety of biological and infectious contaminants. Such significant advances in this field could transform numerous industries, including environmental monitoring, public health, and even food safety. Biological contaminants, which are indeed harmful microorganisms, can be found in various mediums such as water, air, or food supplies. Pathological analysis refers to the comprehensive procedures used to accurately identify pathological conditions based on detailed microscopic, chemical, macroscopic, and other thorough examinations that contribute to our understanding of diseases and contaminants. This multifaceted approach to diagnosis underscores the importance of nano chemistry in modern biomedical science and diagnostics.